Women's empowerment: Staging power resistance in Oshin (2013) - Tisnawijaya, Christy; Kurniati, Geni (LITERA, 2024)
Fictional movies captivated the audience in many ways through their stories and audio-visual. The stories of fictional movies often reflect what happens to our society, and we savor the purification of the hero's tragic flaw. One of which is power relations between males and females. This study explores women's empowerment in Oshin the movie (2013). The narrative is about a seven-year-old girl called Oshin, who is made to work as a maid by her father due to the family's poverty. At first, she is against her father's idea of being separated from her family. She struggles to become a maid until she is accused of stealing and runs away. By watching her mother's efforts as the household pillar, she finally realizes the importance of being an independent female. The movie shows power relations issues regarding filial duty and social stratification. Yet, with the help of Foucault's theory of The Subject and Power (1982), power resistance is a more eloquent outcome to discuss. Thus, this study proposes the stages of power resistance and how the protagonist declares her resilience through traditional gender roles. Moreover, this study uses an interpretative method by scrutinizing each scene that shows power resistance; the discussion reveals that Oshin participates in staging power resistance for women's economic empowerment, which subsequently contributes to her family's economic development. This study concludes that financial independence and women's empowerment are inextricably linked.